Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.5 Rational Expressions - R.5 Exercises - Page 53: 32



Work Step by Step

The given expression is equivalent to: $=\dfrac{y^3-3^3}{y-3}$ Factor the numerator and the denominator then cancel the common factors. Factor the numerator using the formula $a^3+-b^3=(a-b)(a^2+ab+b^2)$ with $a=y$ and $b=3$. : $\require{cancel} =\dfrac{(y-3)(y^2+3y+9)}{y-3} \\=\dfrac{\cancel{(y-3)}(y^2+3y+9)}{\cancel{y-3}} \\=\color{blue}{y^2+3y+9}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.